Pelanggaran Etika Pariwara Indonesia dalam Iklan Dancow 1+ Imunonutri - Praditya, Radika Dava; Ramadhani, Dwi Ardika; Pamungkas, Alam Hanafi Assidiq Andi; Muktaf, Zein Mufarrih (Universitas Muhammdiyah Yogyakarta, 2025)
Advertisements are an effective communication tool to influence consumer behavior, including promoting the Dancow 1+ immunonutri formula milk product. However, advertising must meet the standards of the Indonesian Advertising Ethics to avoid misleading consumers. This research explores ethical violations in the